(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Amidst the Novel Coronavirus 2019 or COVID-19, it is inevitable for customers to change their behaviour, and purchasing online has become a trend. It allows customers to browse and purchase online in their homes while the government works to eradicate the virus’s spread. Hence, this study further attempts to discover the factors influencing adult customers to purchase online amidst the Sta pandemic. Lucia Novaliches Quezon City. The descriptive design is used and suitable in this study. This study aims to determine the factors influencing adult customers to purchase online amidst the Sta pandemic. Lucia Novaliches Quezon City. The instrument used in this study is a focus group online survey using the Google Forms application. The researchers used a purposive sampling focus group online survey using the Google Forms application. The study finds out that customers purchasing online amidst the pandemic at Sta. Lucia Novaliches Quezon City is being affected by several factors such as demographic factors, price, mode of payment, return & refund policy, benefits, reviews and feedback, convenience and comfortability, behaviour, shopping application, and safety and security plays an important role in purchasing online. In conclusion, the pandemic caused many online shopping platforms to grow rapidly. Online shopping is another way to promote and advertise more products and easily reach more people. That became a trend and a new habit of many Filipinos, especially the customers at Sta. Lucia Novaliches Quezon. However, purchasing online has its advantages and disadvantages. That leads to many customers having factors and a change in behaviour in purchasing online.